Experimental investigation of the current plasma lens in the non-uniform magnetic field - Belan, V.N.; Butenko, V.I.; Ivanov, B.I.; Kiselev, V.A.; Linnik, A.F.; Onishchenko, I.N.; Prishchepov, V.P.; Yegorov, A.M. (Вопросы атомной науки и техники, 1999)
The ion focusing by the uniform (along
the radius and length) current lens was investigated
elsewhere. In this work the more complicated,
strongly non-uniform (in z-direction) case is considered
when parameters of the focusing channel (the current
channel radius, current density, focusing azimuthal
magnetic field) are changed sufficiently on the focusing
distance by the external magnetic field. Theoretically
the problem is being solved in details in Ref. [4]. In this
work the numerical calculations and experimental
investigations are presented.